(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current stress status of medical staff and some associated factors at Thanh Ba District Medical Center in 2024. Subjects and methods: A cross-sectional interview design was conducted with 173 healthcare staff, utilizing the DASS-21 scale to assess stress levels and univariate logistic regression to analyze associations. Results: Among the 173 medical staff, the stress prevalence was 19.2%. Of these, mild stress accounted for 51.5%, moderate stress for 27.3%, and severe stress for 21.2%. There was a statistically significant difference in stress levels between doctors and nurses, technicians/pharmacists (p<0.05). Factors associated with stress included: Work factors: Fear of making mistakes in patient treatment posed the highest risk for stress, with OR=7.21 (95% CI: 3.15–16.5); Workplace relationships: Receiving limited support from colleagues was the strongest risk factor for stress, with OR=9.42 (95% CI: 3.30–26.9); Work-family conflict: Difficulty requesting leave for family emergencies was associated with stress, with OR=4.84 (95% CI: 1.92–12.1). Working environment: A noisy and disorganized workplace presented the highest environmental risk, with 28.6% prevalence and OR=1.98 (95% CI: 1.03–4.68). Conclusions: The study results emphasize the necessity of developing comprehensive stress-reduction strategies, including reasonable work allocation, alleviating pressure from legal responsibilities, improving the working environment, and enhancing peer support. These measures not only help improve the mental well-being of healthcare workers but also ensure the quality of patient care.